The Authority of Oil and Gas Special Task Force as a Company Holder and Implementers of Upstream Oil and Gas Bussiness Activity: a Juridical ViewPoint - Luthfia, Fanisa; Triani, Triani (Lembaga Contrarius Indonesia, 2023)
In 2001, Law No. 22 of 2001 concerning Oil and Gas was enacted, which aimed to regulate Pertamina's authority in the oil and gas sector, as well as grant rights and authority to other domestic and foreign oil companies. Consequently, this limited Pertamina's ability to explore and exploit new oil fields. This article adopts a normative juridical research method, which seeks to address existing legal issues through this approach. The research method includes the Case Approach, Statute Approach, and Conceptual Approach, which will be utilized by the author. Through this approach, the compatibility between legal provisions and their implementation will be examined. The findings indicate that, according to statutory regulations, the government agency responsible for upstream oil and gas activities in Indonesia was initially the Executive Agency for Upstream Oil and Gas Business Activities (BP Migas), which was later replaced by the Special Task Force (SKK) for Oil and Gas. The Constitutional Court dissolved BP Migas based on the decision that BP Migas solely controlled and supervised oil and gas management, without engaging in direct management activities. This led to a relationship model between BP Migas, as a representative of the state, and business entities, which contradicted the constitutional principle of state control over oil and gas natural resources.